KERAGAAN RANTAI PASOK TEPUNG KELAPA PT. UNICOTIN DI SULAWESI UTARA - Monalisa Anny Luntungan; Agnes Estephina Loho; Rine ., Kaunang (Sam Ratulangi University, 2021)
This study aims to describe the supply chain performance of coconut flour at PT. UNICOTIN by focusing on supply chain flow. This research was conducted from December 2019 to September 2020 at PT. UNICOTIN, North Sulawesi. The research method used in this research is case study method. The data used in this study are primary data and secondary data. The data analysis technique used in this research is descriptive analysis method to describe the supply chain performance at PT. UNICOTIN. Supply chain actors are (a) Suppliers of coconut raw materials including farmers, concurrently farmers, collectors, (b) PT. UNICOTIN in Airmadidi, (c) Head office of PT. UNICOTIN in Jakarta, (d) large importers in Germany, Holland, England, Poland, Egypt, Russia and China, and small numbers of other importers who have their respective roles. The supply chain flow consists of information flow starting from the need for coconut flour from the importer to the Jakarta Head Office, the flow of products starting from the supply of raw coconut materials from the supplier, and financial flows in the form of payments from the importer to the Jakarta head office.Â